Image-Symbols in the Tatar Poetry Between the 1920s-1930s - Marsovna Yusupova, Nurfiya; Firdinatovna Ganieva, Aygul; Khaliullovna Minnullina, Fatima; Radifovna Nadyrshina, Leysan; Faikovich Yusupov, Ayrat (International Journal of Engineering and Technology, 2018)
This article reveals the functional and semantic field of image-symbols in the Tatar poetry of the 1920s-1930s as exemplified by the poetic texts of Hadi TaqtaÅŸ, Musa CÉ™lil, Hasan Tufan and Ahmed Faizi. The structural and semantic field of the image-symbols formed in the literature between the 1920s and the 1930s significantly differs from the artistic and aesthetic search of the previous periods in the development of literature. Avant-garde experiments with the form of verses of the 1920s, complex literary devices and techniques, as well as the possibility of creating an image from a large number of mosaic details led poets to folklore image-symbols. At the same time, the authors observed the diversity of ideological images that often serve as symbols and structure-forming components in the structure of a poetic text. The research aims to study folklore and ideological image-symbols in the Tatar poetry of the 1920s-1930s and to reveal their structural-semantic and functional field in poetic texts. The scientific novelty of this article is determined by a different approach to the study of the system of images in poetic works, i.e. in the course of the study, the authors focus their attention on the symbolic use of images as structure-forming components. Within the framework of this research, the authors have proved that folklore and ideological symbols act as structure-forming components and are perceived as an opportunity to change artistic paradigms, restore ideological and philosophical depth, polysemy, the possibility of double interpretation and national traditions of the Tatar poetry. The fundamental method used in the course of this study is the hermeneutic approach that guides the readerâ€™s receptive activity to the analysis of principles and techniques for creating images and image-symbols.Â